2018
DOI: 10.1016/j.scs.2017.10.027
|View full text |Cite
|
Sign up to set email alerts
|

Building integrated agriculture information modelling (BIAIM): An integrated approach towards urban agriculture

Abstract: Urbanisation is transforming human societies in many ways. Besides bringing benefits to people in cities, it also has negative impacts such as food security. One way to meet the challenge is urban agriculture; however, traditional agricultural practices are not suitable within urban areas due to limited availability of land. Therefore, the alternative option is to grow crops inside or on top of buildings, e.g. building integrated agriculture (BIA). But, there is limited research and information available for d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(9 citation statements)
references
References 62 publications
(76 reference statements)
0
7
0
Order By: Relevance
“…Although it is likely that, in all cases, a higher productivity will be obtained per unit area, there will be substantial differences in terms of product quality for different crops and the overall mass harvested, such as for crops capable of multiple harvests. Furthermore, not all plants are suitable for vertical production as the available height for plant development is limited [24].…”
Section: Discussionmentioning
confidence: 99%
“…Although it is likely that, in all cases, a higher productivity will be obtained per unit area, there will be substantial differences in terms of product quality for different crops and the overall mass harvested, such as for crops capable of multiple harvests. Furthermore, not all plants are suitable for vertical production as the available height for plant development is limited [24].…”
Section: Discussionmentioning
confidence: 99%
“…In [40], the authors suggested the validity of VF atmosphere reasons which plant development inside the building structures includes less encapsulated energy and deliveries less contamination than some horticultural practices on normal land. The study in [41,42] proposed utilizing high rises buildings to develop food called Skyfarms or yield production factories. The work in [43,44] showed a method is to use a solitary tall glasshouse plan with numerous racks of yields stacked vertically.…”
Section: General Structure Of Vertical Farmmentioning
confidence: 99%
“…Addressing the interface of architecture and agriculture, Khan at el. [69] present their developments to integrate urban agriculture in form of building integrated agriculture into BIM considering requirements of the plants, e.g., temperature and nutrients.…”
Section: State Of the Artmentioning
confidence: 99%